Analisis Pengaruh PDRB dan Kunjungan Wisatawan Terhadap PAD (Periode 2011-2024) - Airul Syahrif; Selly Kudrati Ningsih (Journal of Trends Economics and Accounting Research, 2026)
This study analyzes the influence of Gross Regional Domestic Product (GRDP) and tourist arrivals on Local Own-Source Revenue of Makassar City over the period 2011–2024. The research framework integrates GRDP and tourist arrivals as the two primary engines shaping PAD. GRDP serves as an indicator of rising household and government consumption, while high tourist arrivals act as a multiplier effect expected to drive PAD growth in Makassar City. Employing multiple linear regression with 14 years of time-series data, the study tests the significance of GRDP and tourist arrivals as independent variables on PAD as the dependent variable. The analysis reveals that the model with two independent variables yields R² = 0.954 and F-statistic = 115.192 (p < 0.001), indicating the model is highly statistically significant. GRDP demonstrates a dominant effect with an unstandardized coefficient β = 0.013 (p < 0.001) and standardized β = 0.908, whereas tourist arrivals exhibit a secondary influence with an unstandardized coefficient β = 0.074 (p = 0.003) and standardized β = 0.244. The findings confirm that these two economic sectors, GRDP and the number of tourist arrivals, are the main drivers of PAD growth in Makassar City. Policy implications underscore the importance of sustainably developing economic growth and tourism as the foundation for regional revenue expansion, while optimizing the tourism sector's potential as a less volatile supplementary growth source.